Cover Feature: Formation and Modulation of Nanotubular Assemblies of Oligourea Foldamers in Aqueous Conditions using Alcohol Additives (ChemPlusChem 10/2020). Issue 10 (14th August 2020) - Yoo, Sung Hyun; Collie, Gavin W.; Mauran, Laura; Guichard, Gilles
Abstract : The Cover Feature shows nanotubular structures, as visualised by electron microscopy and X‐ray crystallography, formed from the self‐assembly of an amphiphilic helical oligourea foldamer (artificial folded oligomer) in aqueous conditions. Importantly, it was possible to control the shape and morphology of the resulting tubular assembly—from single short tubules to extended tubule bundles (i.e., fibres)—by modulating the polarity of the aqueous environment through the use of alcohol additives. More information can be found in the Full Paper by G. Guichard and co‐workers .